A case of not just Pott's disease. (August 2021) - Greene, William; Prager, Martin; Richardson, Marlin
Spinal tuberculosis (TB) is a rare cause of vertebral osteomyelitis in the developed world. Co-infections with other microorganisms are seldom reported in the literature. Here we report a case of Mycobacterium tuberculosis and Streptococcus anginosus causing acute on chronic vertebral osteomyelitis with an epidural abscess.